IMPLEMENTASI ASEAN CYBER CAPACITY PROGRAM (ACCP) DALAM MENANGGULANGI KEJAHATAN SIBER DI INDONESIA 2016-2020 - Sofyan, Ridwan; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research analyzes how the ASEAN Cyber Capacity Program (ACCP) was implemented in tackling cyber crime in Indonesia in 2016-2020. ACCP is a collaboration in increasing the regional cyber capacity of Southeast Asian countries. This regime was initiated by Singapore in October 2016 and in followed by all ASEAN countries by sending several representatives from these countries. In recent years, Indonesia and other ASEAN countries have often received cyber attacks from irresponsible parties. Therefore, this research aims to see how ACCP is implemented in tackling cyber crime. This research uses qualitative research methods with primary data obtained through interviews, as well as secondary data originating from various existing reading sources such as books, journals, newspapers and others. This research uses a liberalism perspective, nation-state level of analysis and international regime theory. The results of this research show that Indonesia implements ACCP in several ways, namely, by participating in discussion facilities and sharing information on cyber security issues through the Singapore International Cyber Week (SICW) and the ASEAN Ministerial Conference on Cyber Security (AMCC) to explore deeper issues regarding cyber security in Southeast Asia, then providing training and improving the quality of the national Computer Emergency Response Team (CERT) through the ASEAN-Singapore Cybersecurity Center of Excellence. After five years, ACCP cooperation is still developing and becoming a facility for ASEAN countries to exchange information, and improving cyber security. Keywords : ASEAN Cyber Capacity Program, Cyber Crime, Cyber Security